Case Study on need of ICT in Teaching Learning Process - Kumbar, S. S.; Bidnurkar, A.; Tamhane, K. N.; Kumbar, R. B. (Journal of Engineering Education Transformations, 2018)
ICT has become integral part of life, the initiation of Information and communication technology has made tremendous changes in 21st century. All the fields of the life are influenced by these digital phenomena. The advent of ICT in teaching and learning helped to improve the quality of education, where teaching and learning eventually became an engaging active process related to real life. ICT is helping everybody to fulfill all kind of needs, As a result ICT learning is not limited to four walls of the classroom, information transmission takes place even outside the classroom. This paper will highlight the impact of ICT on teaching learning process. Also an attempt to check the likings of the students to make learner centric approach. Traditional method is compared with the ICT based learning. Analysis is carried out for the class strength of 60. It gives an idea of interest of the students towards the ICT in the teaching learning process. It is concluded that involvement of ICT is required in the process to enhance the knowledge dissemination and also it will help for the creativity and application.